Striving for authenticity the foundation and dynamics of the AlDub Nation fandom - Cabbuag, Samuel (Plaridel, 2023)
Access online through this link: https://www.plarideljournal.org/article/striving-for-authenticity-the-foundation-and-dynamics-of-the-aldub-nation-fandom